EVA (Company and Shareholder Value Indicator) - Gaytán Cortés, Juan (Mercados y Negocios, 2025)
Economic Value Added (EVA) originates as a value-based measure of performance, comparing the profitability obtained by a company with the opportunity cost of capital used to support its tangible and intangible resources. EVA measures the actual creation of shareholder value by a company. In other words, it is not enough for a company to be profitable; it must also cover the opportunity cost of investing in its tangible and intangible resources.